Clinical and pathological profile of Gallbladder Cancer (GBC) and Gallstone disease GSD) among the patients admitted in tertiary care institute in Kolkata - Abhishek Mohata; Mrinmoy Adhikary; Ranajit Bari; Shubho Chowdhuri; Pulak Kumar Jana; Vinoth Gnana Chellaiyan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Background: Gallstone disease (GSD) is one of the most common surgical problems throughout the world. The rise in gallstone disease burden and its wide spectrum of non-specific presentation makes the disease more challenging. Gall bladder cancer (GBC) is a common cancer in the northern and North-eastern States of India. The six cancer registries of the Indian Council of Medical Research (ICMR) (1990-1996) show a 10 times lower incidence of GBC per 1 00 000 in South India compared with the North. The objective of present study was to assess the epidemiological and pathological profile of GSD and GBC patients of Eastern India visiting tertiary care hospital of Kolkata.Method: This cross-sectional observational study was conducted, over a period of 18 months, at a tertiary referral hospital of Kolkata. In this study, 66 gallstone disease patients and 24 gallbladder cancer patients who undergone surgery were included in the study after their written informed consent. Data on their demographic and pathological profile, type of gallstones, their number and staging and type gallbladder cancer were collected. Results: GSD GBC were found to afflict females, Male to female ratio was 1:2 1:3 for GSD and GBC respectively. We found that nearly half (45.4%) GSD patients were in the age group of 21-40 years and more than half (58.6%) GBC patients were in age group of 41-60 years. Majority of GSD patients had multiple stones (57.6%) and cholesterol stones were most common (59.1%). Out of 24 GBC patients, nearly one-third (33.3%) had stage II cancer and only 12.5% patients had stage IV cancer. More than one-fourth (29.2%) GBC patients had poorly differentiated carcinoma.Conclusion: The results of this study reaffirm that female gender is a strong predisposing factor for GSD and GBC and patients in their fourth decade, are more at risk. Large population based multicentric analytical study is necessary to strengthen this study findings.